Anthelmintic resistance of horse strongyle nematodes to fenbendazole in Lithuania - Evelina Dauparaitė; Tomas Kupčinskas; Marian Varady; Saulius Petkevičius (Acta Veterinaria Scandinavica, 2022)
Abstract Background Control of strongyle infections presents a global challenge for horse practitioners due to the development of anthelmintic resistance (AR), however comprehensive information on AR in Lithuania is still lacking. The aim of this study was to assess the current situation of fenbendazole (FBZ) AR in horses at stable level in Lithuania. Results Faecal samples from 121 horses from six stables were examined using the Mini-FLOTAC method. Of these, 89 horses met the inclusion criteria that included strongyle faecal egg counts (FEC) exceeding 200 eggs per gram (EPG). Faecal egg count reduction tests (FECRTs) were performed in these. AR was evaluated at horse stable level based on faecal egg count reduction (FECR) and the lower limit of the 95% credible interval (LLCI) using the Bayesian hierarchical model. This study confirmed that strongylids (Cyathostominae (CYA)) resistant to FBZ are pervasive in Lithuania. FBZ was ineffective in three of the six stables (FECR 77.1–79.0%; 49.8–99.8 LLCI), was suspected to be ineffective in one stable (FECR 93.6%; 85.4–100 LLCI) and was effective (FECR 99.8–100%; 99.8–100 LLCI) in two stables. FEC showed a significant (P < 0.01) difference between the treatment and control groups. Only CYA larvae were detected in larval cultures derived from strongyle-positive faecal samples collected 14 days after treatment of a test group with FBZ. Conclusion This in vivo study showed that resistance to FBZ in the treatment of strongyle nematodes is prevalent in horse stables in Lithuania. These findings should guide the implementation of more sustainable management of strongyle infections in horses in Lithuania.